Stored grain protection: cases studies in Portugal - Carvalho, Maria Otilia; Cambeiro, Ana Filipa; Fradinho, Patrícia; Magro, Ana; Teixeira, Bárbara; Mendes, Rogério; Mourato, Miguel Pedro (Julius-Kühn-Archiv, 2018)
Considering the edibility of insects’ species associated with storage ecosystem, chemical control methods can be easily replaced by environmental and economically sustainable alternatives. Use of biogenerated atmospheres is an inexpensive method that tolerates insect presence. In Portugal, during one year, hermetic bags were used to store paddy under 65-75-85% relative humidity (RH) and 14-17-24ºC temperatures. Brown rice infested with Sitophilus zeamais adults was placed inside the hermetic bags. Biogenerated atmosphere was naturally produced inside the hermetic bag, at 85% RH, with low O2 and high CO2 contents, showing that S. zeamais can survive but has no progeny at 14º-17ºC, or attained 100% mortality before producing progeny at 24ºC. The most abundant fungi isolated were Alternaria alternata and Epicoccum nigrum. The results showed the importance of the RH on changes in atmospheric gas content of paddy, due to biological agents’ activity. Analysing the edibility of insects species associated with stored grain, preliminary studies were carried out to evaluate the nutritional value of immatures stages of Tribolium castaneum. Larvae of T. castaneum had a content of 21.4% protein, 9.1% lipids, 8.8% fiber, and a relevant content of eight essential amino acids and also manganese and copper. The edibility of insects must be consider given their high nutritional value, low emissions of Green House Gases (GHGs), low requirements for land, and by reducing and mitigating the need for chemical control.